Training and Mentoring in the Development of Test Instruments for Measuring Learning Outcomes of Muhammadiyah School - setyaedhi, hari; Rusijono, Rusijono; Khotimah, Khusnul (International Journal of Community Service Learning, 2023)
This community service learning program is collaboration between the Curriculum and Educational Technology Department of the Faculty of Education Sciences. A key issue facing most SMA and SMK Muhammadiyah school teachers is their lack of knowledge and understanding on how to develop valid and reliable test instruments. This research aims to enhance the knowledge of SMA and SMK Muhammadiyah teachers in developing learning assessment instruments. The Blended Learning method was applied for 32 hours of lessons that involved lectures, Q&A discussions, assignments, practical work, and tests. A total of 12 teachers from SMA and SMK Muhammadiyah schools took part in the program. The research method used was the One-Group Pretest-Posttest Design, which is a type of pre-experimental research design. Data drawn from the pretest and posttest results were analyzed using the t-test. Following the smooth implementation of training and mentoring, a key conclusion is that the community service learning program has successfully met its expected outcome of enhancing the teachers’ ability to develop test instruments. This is evidenced by a significant increase in posttest scores compared to pretest results at Sig. (2-tailed) = 0.001 < 0.05.